2013
DOI: 10.3892/or.2013.2940
|View full text |Cite
|
Sign up to set email alerts
|

Association of the p53 codon 72 polymorphism with clinicopathological characteristics of colorectal cancer through mRNA analysis

Abstract: TP53 represents a suitable candidate for a colorectal cancer susceptibility locus. The polymorphism in the p53 72nd codon involves a proline to arginine substitution, leading to changes in gene transcription activity, interaction with other proteins and modulation of apoptosis. Studies evaluating the association between this polymorphism and colorectal cancer (CRC) have shown inconsistent results, and none have evaluated the mRNA status of TP53. The aim of the present study was to evaluate the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…However, smaller but more recent studies have found Pro/Pro and Pro/Arg genotypes associated with increased risk of CRC (OR = 4.29; CI 95% : 2.77-6.63; p < 0.001) among 249 CRC patients and 245 healthy controls of a mixed population of Russians and Kazakhs [123]. These results are in consonance with previous study in 322 Spanish controls and 374 cases (OR = 1.34; CI 95% : 0.98-1.84; p = 0.066) [157]. The 72R allele was also an independent predictor for recurrence (OR = 3.83; CI 95% : 1.02-14.35; p = 0.046) in 121 Brazilian CRC patients [158].…”
Section: Q Chromosomal Armsupporting
confidence: 89%
See 1 more Smart Citation
“…However, smaller but more recent studies have found Pro/Pro and Pro/Arg genotypes associated with increased risk of CRC (OR = 4.29; CI 95% : 2.77-6.63; p < 0.001) among 249 CRC patients and 245 healthy controls of a mixed population of Russians and Kazakhs [123]. These results are in consonance with previous study in 322 Spanish controls and 374 cases (OR = 1.34; CI 95% : 0.98-1.84; p = 0.066) [157]. The 72R allele was also an independent predictor for recurrence (OR = 3.83; CI 95% : 1.02-14.35; p = 0.046) in 121 Brazilian CRC patients [158].…”
Section: Q Chromosomal Armsupporting
confidence: 89%
“…The second most investigated polymorphism in TP53 is probably the 16 bp duplication located in intron 3 (p53PIN3 A2 allele; rs17878362) [161], which has been associated with increased risk of CRC (OR = 1.55; CI 95% :1.10-2.18; p = 0.012) in 322 controls and 374 cases [157].…”
Section: Q Chromosomal Armmentioning
confidence: 99%
“…A SNP in MDM2 (SNPT309G), a negative regulator of p53, alone or in combination with p53 has been reported to associate with different carcinomas and progression of disease [14,18,22,23,25,[27][28][29][30]. Over the last decade, studies have reported the role of p53 R72P and MDM2 T309G polymorphisms as risk factor for colorectal carcinoma [14,15,19,[23][24][25]. To our knowledge there is no study which have shown the impact of p53 R72P and MDM2 T309G alone or in combination on the CRC patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) at codon 72 exon 4 of TP53 (rs1042522) has intensively been studied for its association with the risk and progression of CRC [10][11][12][13][14][15]. This polymorphism alters a single amino acid; found either in homozygous arginine (Arg/Arg; G/G), or homozygous proline (Pro/Pro; C/C) and/ or heterozygous proline/arginine (Arg/Pro; G/C).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivating point mutations and single nucleotide polymorphisms of TP53 can also confer worse prognosis, which has confounded attempts to associate TP53 expression with survival. 26 A more recent study assessed p53 functionality, which was associated with improved survival on multivariate analysis. TP53 is influenced by multiple effect modifiers; one recently identified is casein kinase Ia (CKIa) (CSNK1A1), which is a protein kinase that targets cytoplasmic b-catenin for degradation, preventing activation of WNT signaling.…”
Section: Chromosomal Instabilitymentioning
confidence: 99%